(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Robotics is one of the technologies of the fourth industrial revolution, which has a wide range of applications, from household chores to manufacturing and healthcare to entertainment and space exploration. The purpose of the study is to determine and evaluate the repeatability and positioning accuracy indicators of the robotic system when reproducing the movements of the hand repeating a human hand. The article conducts a comparative analysis of the methods and software control algorithms for creating feedback of robotic system electromechanical control gears displacement, and provides the rationale for the choice of physical equipment for the technical experiment. This article describes the plan of stages of the experimental research, the research bench, presents the systematized results of the research, conclusions and suggestions for practical application.